(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: Liver is the principal site of many metabolic activities and is vulnerable to many metabolic, toxic, microbial and circulatory insults. It is frequently involved in metastatic spread of malignancies from all parts of body. Aims: This study aimed to analyze histopathological spectrum of liver diseases in autopsy cases, and correlate with the clinical findings wherever available. Materials and Methods: It was an observational study conducted over a period of 2 years on 283 autopsy cases in department of Pathology of a tertiary care teaching institute in central India. Liver specimens were included in study irrespective of age, sex and cause of death. After fixation in 10% formalin the sections from representative area were submitted for processing, Hematoxylin and Eosin-stained sections were subjected for microscopic examination. Results: Total 283 liver autopsy cases studied showed predominance of male (68.65%). Maximum cases were in the age group of 21 to 30 years (20.14%) followed by 31 to 40 years (18.28%). Fatty change was evident in a majority (32.08%) of the cases while a remarkable (26.49%) number of cases showed changes of congestion on histological examination. Massive hepatocellular necrosis and midzonal necrosis were seen in 2 cases each. Tubercular granulomas and metastasis of adenocarcinoma were seen in 3 cases each. Conclusion: Histological analysis of liver is important learning objective for pathologists to study silent diseases of liver which are incidentally seen in histopathology.